Influence of highways on the spread of Sars-CoV-2 in the municipalities of Northeast Minas Gerais (Research, Society and Development, 2021)
It is a fact that the influence of the road flow is correlated with the spread of several communicable diseases, and may keep the same relationship for the spread of SARS-CoV-2 in the municipalities. The present work aims to verify the influence of the BR-116, BR-418 and BR-367 highways in the spread of SARS-CoV-2 in 73 municipalities in the Northeast region of Minas Gerais, and in the pole city, Teófilo Otoni -MG. For this purpose, several variables related to the disease were verified, such as: confirmed cases, deaths and days until the disease settled in a city. Still, an evaluation was carried out on the existence of a correlation between a variable referring to the highway and one referring to disease, with the obtaining of the Pearson and Spearman correlation indices, and finally a hypothesis test was carried out, aiming at obtaining ranking of highways. Based on the calculations performed, the BR-116 and BR-418 presented themselves as the most influential highways in the spread of the virus among the municipalities in the study region. As for the neighborhoods in the city of Teófilo Otoni- MG, BR-418 demonstrated a greater influence on the spread of SARS-CoV-2 than BR-116. The analysis proved to be relevant for a better understanding of how COVID-19 propagates in the cities studied through the highways, which can facilitate the decision making of public managers in the implementation of sanitary measures in these places.